2013
DOI: 10.1007/s00232-013-9621-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Trace Elements and Heavy Metals in Patients with Acute Hemorrhagic Stroke

Abstract: Trace elements are essential components of biological structures, but alternatively, they can be toxic at concentrations beyond those necessary for their biological functions. Changes in the concentration of essential trace elements and heavy metals may affect acute hemorrhagic stroke. The aim of this study was to measure serum levels of essential trace elements [iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), and magnesium (Mg)] and heavy metals [cobalt (Co), cadmium (Cd), and lead (Pb)] in patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 47 publications
2
21
1
Order By: Relevance
“…Compared with the controls, serum iron levels were significantly lower in patients with ICH in the present study, rather than higher as found in patients with acute hemorrhagic stroke 19 and in rat models of ICH 18 . The opposite results might be partly due to the differences in age (44 ± 6 vs. 56 ± 12) and sex (female/male:12/14 vs. 28/72) of patients and species (patients vs. rats), therefore further investigations about the relevant causes are needed.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Compared with the controls, serum iron levels were significantly lower in patients with ICH in the present study, rather than higher as found in patients with acute hemorrhagic stroke 19 and in rat models of ICH 18 . The opposite results might be partly due to the differences in age (44 ± 6 vs. 56 ± 12) and sex (female/male:12/14 vs. 28/72) of patients and species (patients vs. rats), therefore further investigations about the relevant causes are needed.…”
Section: Discussioncontrasting
confidence: 77%
“…The increased total serum iron levels have been observed in rat models after experimental ICH 18 , and also the measurements of this indicator in serum are easy to be conducted in clinic. However, it is really surprising that not much information about the changes in serum iron in patients with ICH is available, except for a recent study which was conducted in the patients with acute hemorrhagic stroke using atomic absorption spectrophotometry 19 . Tf is unique in chelating iron with very high affinity.…”
Section: Discussionmentioning
confidence: 99%
“…e serum As concentrations in Vietnam were higher than those in both healthy people and patients with various diseases reported in Belgium [20]. As for other elements, mean concentrations of Pb and Cd were from 6.44 to 0.52 µg/l, respectively, which were comparable or higher than those reported for patients with acute hemorrhagic stroke in Turkey [21]. In general, toxic element concentrations in serum from Ha Nam were in the range of those reported in human samples with toxic element-associated diseases.…”
Section: Contamination By As and Other Elements In Humanmentioning
confidence: 55%
“…Moreover, serum ferritin concentrations have a direct relationship with stroke in women [7]. A previous study indicated that an increase occurs in iron storage before stroke [21].…”
Section: Discussionmentioning
confidence: 95%
“…A preliminary study revealed that high iron levels increase the risk of cerebrovascular attack. The effects of trace elements and heavy metals on patients with acute hemorrhagic stroke has been studied [7]. Rapid identification of stroke patients in the emergency department is an essential part of therapy.…”
Section: Introductionmentioning
confidence: 99%